Stress, Glucocorticoids and Bone: A Review From Mammals and Fish - Suarez-Bregua, Paula; Guerreiro, Pedro Miguel; Rotllant, Josep (Frontiers in Endocrinology, 2018)
Glucocorticoids (GCs) are the final effector products of a neuroendocrine circuit called HPA axis governing energy balance and stress response. From a physiological point of view, basal GCs levels are essential in the intermediary metabolism and participate in the development and homeostasis of a wide range of body tissues, including skeleton. Numerous studies have demonstrated that GC hormones exert a positive role during bone modeling and remodeling as they promote osteoblastogenesis to maintain the bone architecture. Although the pharmacological effect of the so-called stress hormones is widely reported, the role of endogenous GCs on bone mineral metabolism as result of the endocrine stress response has been largely overlooked across vertebrates. In addition, stress responses are variable according to the stressor (e.g., starvation, predation, environmental change), life cycle events (e.g., migration and ageing) and differ among vertebrate lineages, which react differently according to their biological, social and cognitive complexity (e.g., mineral demands, physical and mental stress). This review intends to summarize the endogenous GCs action on bone metabolism of mammals and fish under a variety of challenging circumstances. Moreover, we discuss the regulatory loop between GCs and the parathyroid hormone (PTH) family peptides, and other key regulators of mineral homeostasis and bone remodeling in vertebrates.